The Influence Of Lifestyle Brands On Generation Z Consumer Behavior For Tuku Coffee Products In Bogor Regency - Arif Igo; Kelty Nurdarani Loves (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of lifestyle brand on Generation Z consumer behavior toward Kopi Tuku products in Bogor Regency. The increasing trend of coffee consumption among Generation Z is not only influenced by product quality, but also by the brand’s ability to represent lifestyle, social identity, and consumer preferences. This study employs a quantitative approach using a survey method through questionnaire distribution to respondents who meet the criteria, namely Generation Z aged 17–27 years who have purchased Kopi Tuku products in Bogor Regency. The sampling technique used is purposive sampling with a total of 100 respondents.The data were analyzed using simple linear regression supported by t-test and coefficient of determination (R²). The results show that lifestyle brand has a positive and significant effect on Generation Z consumer behavior toward Kopi Tuku products in Bogor Regency. This indicates that the stronger the consumer perception of lifestyle brand, the higher the tendency of consumer behavior, such as purchase intention, loyalty, and purchase decisions.